A Possible Interpretation for the High Catalytic Activity of Heat-Treated Non-Precious Metal Nx/C Catalysts for O 2 Reduction in Terms of Their Formal Potentials - Paez-Collio, M; Paez-Collio, M; Zagal-Moya, J; Zagal-Moya, J; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Gulppi-Cabra, M; Gulppi-Cabra, M; Ponce-Hormazabal, I; Venegas-Toledo, R (2012)
In this paper we compare the catalytic activitites of untouched metal macrocyclic and pyrolyzed catalysts for ORR in acid versus the formal potential of the catalyst and find in general that the catalysts reported in the literature exhibiting more positive formal potentials are more active for ORR. These trends observed could serve as a hint for the development more active non-precious metal catalysts for fuel cells. © 2012 The Electrochemical Society.